Assessment of the Effectiveness of Green Infrastructure Interventions to Enhance the Ecosystem Services in Developing Countries - Diego Paredes Méndez; Modesto Pérez-Sánchez; Francisco Javier Sánchez-Romero; Oscar E. Coronado-Hernández (Urban Science)
Cities face complex challenges, including climate change, population growth, urbanization, natural hazards, pollution, biodiversity degradation, and inadequate public services. Hydro-meteorological hazards such as floods, landslides, droughts, and heat waves are among the most significant risks, with floods often causing severe impacts and loss of life. Traditional responses, typically hard engineering infrastructures, dominate mitigation efforts. However, green infrastructures (GIs) offer sustainable, cost-effective solutions with added benefits, enhancing ecosystem services and societal well-being. Despite their effectiveness, GI implementation is slow, particularly in developing countries, due to the complex construction, operation, and maintenance processes, alongside knowledge gaps. This study proposes an assessment framework to evaluate GI performance in mitigating hydro-meteorological hazards. By integrating hydrologic–hydraulic modeling, the framework analyzes baseline and post-intervention conditions, offering valuable insights into hazard reduction and cost-effectiveness. Key indicators for assessing GIs include runoff volume reduction, peak flow reduction, flood node mitigation, and increased time to peak flow. Studies show that GIs can achieve reductions of 30–90%. This framework aims to advance the adoption of GIs by providing practical tools to assess and monitor its performance in hazard management.